Hillslope evolution of heterolithic landscapes: investigating processes and controls on geomorphic development of staircase landscapes - McCarroll, Nicholas Reilly (Kansas State University, 2024)
This dissertation explores different components commonly associated with layered landscapes, using the Flint Hills in northeast Kansas as a natural laboratory and inspiration. The geology of the Flint Hills results in a distinctive stair-step hillslope profile covered in large rock fragments and boulders that armor the slopes. The research presented in the dissertation focuses on three components of layered landscapes: boulder armor transport, boulder armor production, and the influence of stratigraphy on landscape evolution. The investigation employs a combination of thorough fieldwork, geochronologic techniques, and computer modeling to gain deeper insights into these areas. In Chapter 2, I find that boulder armor in soil-mantled landscapes like the Flint Hills is primarily transported downslope through creep processes. The complex relationship between boulder size and distance downslope suggests that boulders undergo in-situ weathering via fragmentation. Chapter 3 extends the timeline, finding that boulder armor and bedrock bench surfaces date back to the Late Pleistocene during the Last Glacial Maximum. This study suggests that block production and transport were most active during this glacial period, with subsequent warming leading to a slowdown in the system. The boulder armor on the hillslopes is considered relict features representing a time of increased activity. Chapter 4 involves modeling layered landscapes, providing insights into their long-term dynamics. The results suggest that the efficiency of boulder armor is related to the spacing between layers and the transport efficiency of the boulders. While layered landscapes attempt to establish a dynamic steady state, boulder armor and stratigraphic architecture may prevent them from achieving such a state for extended periods of geologic time. When the findings of these chapters are considered together, it is suggested that boulder armor production may be an intrinsic part of layered landscapes influenced by glacial climates. In locations where moisture conditions are suitable, creep processes spread the boulders out and down the slopes to form discrete boulder armor, rather than a blanket of colluvium like a boulder field. Future research can further explore the timing of bench and boulder production across all the bedrock benches on the hillslope to test whether boulder production is a bottom-up base-level process or a top-down climate-driven process. The Flint Hills, along with layered landscapes in general, offer valuable opportunities for advancing our understanding of geomorphology.
Keywords: Boulder; Kansas; Flint Hills; Hillslope; Layered landscapes; Geochronology